GEOmedia intervista Antonio Bottaro sul tema degli Initial Services di Galileo - Redazione MediaGEO (GEOmedia, 2017)
GEOmedia interviewed Antonio Bottaro, the head of Research and Development of Sogei, the in-house company of the Ministry of Economy and Finance, which for 40 years working for innovation, with a cutting-edge industrial design and advanced IT solutions digitization of the Public Administration. Antonio Bottaro is also CEO of GEOWEB S.p.A.